Gamification as a Pedagogical Tool for Enhancing Critical Thinking and Problem-Solving Skills in STEM Education: A Case Study of High School Classrooms - Sahito, Farzana Zahid; Sahito, Zahid Hussain (Journal of Development and Social Sciences, 2024)
This study aims to explore the effectiveness of modern teaching methods in enhancing student engagement and critical thinking in STEM education. STEM education is a global priority due to its role in preparing students for the knowledge-based economy. Traditional methods of teaching STEM, such as lectures, often fail to engage students or develop their analytical and creative skills, which are essential for the 21st century. A review of current teaching practices in STEM was conducted, focusing on the effectiveness of active learning and innovative instructional strategies in improving student interest and cognitive skills. The findings highlight that interactive and student-centered approaches significantly increase engagement, creativity, and critical thinking in STEM subjects. It is recommended that educators adopt more interactive teaching methods, integrate real-world problem-solving, and foster creativity to enhance learning outcomes in STEM education.